2012
DOI: 10.1002/bies.201100161
|View full text |Cite
|
Sign up to set email alerts
|

Contagious cancer: Lessons from the devil and the dog

Abstract: Cancer is generally defined as uncontrollable growth of cells caused by genetic aberrations and/or environmental factors. Yet contagious cancers also occur. The recent emergence of a contagious cancer in Tasmanian devils has reignited interest in transmissible cancers. Two naturally occurring transmissible cancers are known: devil facial tumour disease and canine transmissible venereal tumour. Both cancers evolved once and have then been transmitted from one individual to another as clonal cell lines. The dog … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 94 publications
(99 reference statements)
0
30
0
1
Order By: Relevance
“…CTVT does not metastasize and does not usually cause the death of the host (11). There are many excellent articles on CTVT (12)(13)(14) and reviews comparing CTVT and DFTD (15,16). This review concentrates on DFTD.…”
Section: Immunology Of a Transmissible Cancer Spreading Among Tasmanimentioning
confidence: 99%
“…CTVT does not metastasize and does not usually cause the death of the host (11). There are many excellent articles on CTVT (12)(13)(14) and reviews comparing CTVT and DFTD (15,16). This review concentrates on DFTD.…”
Section: Immunology Of a Transmissible Cancer Spreading Among Tasmanimentioning
confidence: 99%
“…Finally, studies of Tasmanian devil facial tumour disease and canine transmissible venereal tumour have helped us to understand the role of the immune system in shaping tumour evolution and have provided insights into the crucial roles of MHC genes (reviewed in REF. 27).…”
Section: Non-traditional Laboratory Animal Modelsmentioning
confidence: 99%
“…The emergence of DFTD has been attributed to the low level of genetic diversity at the non‐self‐recognising Major Histocompatibility Complex (MHC) immune genes . However, the recent spread of DFTD to areas with genetically disparate devil populations has revealed that DFTD successfully crosses histocompatibility barriers that would normally prevent allograft acceptance demonstrating that devil MHC polymorphism does not affect tumour cell transmission .…”
Section: Transmissible Cancer Invokes Adaptive Changes and Responses mentioning
confidence: 99%
“…The emergence of DFTD has been attributed to the low level of genetic diversity at the non-self-recognising Major Histocompatibility Complex (MHC) immune genes. [85] However, the recent spread of DFTD to areas with genetically disparate devil populations has revealed that DFTD successfully crosses histocompatibility barriers that would normally prevent allograft acceptance demonstrating that devil MHC polymorphism does not affect tumour cell transmission. [86] Rather, DFTD is actively evading the host immune system by down-regulating genes involved in the antigen-processing pathways, resulting in the concomitant loss of cell surface expression of MHC Class I molecules, and escape of immune recognition.…”
Section: Devils Show Genetic Adaptations and Phenotypic Plasticity Tomentioning
confidence: 99%